Increasing the Independence of Santri Through Peer Counseling/ Meningkatkan Kemandirian Santri Melalui Pendampingan Konseling Sebaya (Peer Counseling) - Sadiyah, Elok Halimatus; Hidayati, Fina (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Islamic boarding schools are the best alternative in the world of education to print students to grow and develop into religious, disciplined, and independent individuals. However, the reality in the field of child.lenges is very heavy, so it is necessary to support programs in the effectiveness of increasing independence of students, one of which is through peer counseling (peer counseling). This community service aims to increase the independence of students through peer counseling assistance at the Darunnajah Karangploso Islamic Boarding School in Malang, involving as many as 406 students. The method used is an action research, with the main research question being how peer counseling can improve students' independence. The results of the study prove that the peer counseling model in the Darunnajah Islamic Boarding School in Malang increases the independence of students through: first, students' problem-solving skills with peers. Second, students' ability to learn to control behavior. Third, peers are able to provide social, moral, and emotional support. Fourth, peer groups are able to provide social support and motivation